A Partitioned Chi-square Analysis of Variation in Spanish Clitic Doubling: The Case of dar 'give'. Issue 3 (2nd July 2016) - Aranovich, Raúl
ABSTRACT: In Spanish ditransitive clauses with Dative Clitic Doubling (DClD), the goal may be doubled by a dative clitic pronoun. Applying a chi-square decomposition analysis to examples with the prototypical ditransitive verb dar "give", from a corpus of journalistic language characteristic of River Plate Spanish, I show that DClD is disfavoured when the theme is a bare noun, and also that the distinction between bare and non-bare themes is more statistically significant than the distinction between definite and indefinite themes. The relational effect of definiteness on DClD in clauses with the verb dar is accounted for by extending Hopper and Thompson's (1980) Transitivity Hypothesis to clauses with three arguments.